The Effect of Financial Literacy and Lifestyle on Investment Decisions with Self Control as an Intervening Variable (Student of the Faculty of Economics and Business, PGRI University of Semarang) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The purpose of this study is to find out the Influence of Financial Literacy and Lifestyle on Investment Decisions with Self Control as an Intervening Variable" with a case study on Students of the Faculty of Economics and Business, University of PGRI Semarang. In this study, the approach used is a quantitative approach. The type of research used in this study is causal associative research. The population in this study is all students of the Faculty of Economics and Business, University of PGRI Semarang from all generations, starting from the class of 2021 to the class of 2024. The total number is 1,606. To determine the sample size to use, the researcher used the Slovin formula. Based on the results of the calculation of the number of samples in this study, 94 students of the Faculty of Economics and Business. The sampling technique used is purposive sampling. The data analysis technique in this study uses Partial Least Square (PLS). PLS is a Structural Equation Modeling (SEM) equation model. The results of this study are that Lifestyle has a significant effect on Investment Decisions, Lifestyle has a significant effect on Self Control, Financial Literacy has a significant effect on Investment Decisions, Self Control has a significant effect on Investment Decisions, Lifestyle has a significant effect on Investment Decisions with Self Control as an intervening variable, Financial Literacy has a significant effect on Investment Decisions with Self Control as a variable intervening
Keywords: financial literacy; lifestyle; investment decisions, self control; self control